Percutaneous Management of Inferior Thyroid Artery Pseudoaneurysm Developed after Central Line Placement in a Cirrhotic Patient - Ujjwal Gorsi; Suresh Babu; Tejeshwar Singh Jugpal; Vikas Bhatia; Sunil Taneja (Journal of Clinical Interventional Radiology ISVIR)
Iatrogenic arterial injury is a life-threatening complication of central venous catheterization. We report a rare case of percutaneous ultrasound-guided occlusion of inferior thyroid artery pseudoaneurysm that developed after attempted internal jugular vein cannulation in a cirrhotic patient.